2021
DOI: 10.3390/agriculture11060472
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Fertilizer Use in Relation to Farmers’ Household Characteristics in Three Gorges Reservoir Area, China

Abstract: Non-point source pollution from excessive use of fertilizers in agriculture is a major cause of the eutrophication problem in China. Understanding farmers’ decision-making concerning fertilization and identifying the influencing factors in this process are key to tackling overfertilization and related pollution issues. This paper reports a study on modelling decisions about fertilizer use based on data collected from 200 farmer households in the Three Gorges Reservoir area of China, using a well-fitted artific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
2
9
0
Order By: Relevance
“…Similarly, Moges and Taye [15] explained this correlation as a positive correlation between farmers' education and cognition, and a high cognitive level can improve the adoption level. Most studies have found that young and highly educated farmers have a higher adoption level, which is similar to our conclusion [1,17,24]. However, some studies have found that demographic variables do not continue to play a role, but depend on the complexity of technology [55].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Similarly, Moges and Taye [15] explained this correlation as a positive correlation between farmers' education and cognition, and a high cognitive level can improve the adoption level. Most studies have found that young and highly educated farmers have a higher adoption level, which is similar to our conclusion [1,17,24]. However, some studies have found that demographic variables do not continue to play a role, but depend on the complexity of technology [55].…”
Section: Discussionsupporting
confidence: 87%
“…The inefficient use of chemical fertilizer has always been a major cause of agricultural environmental pollution [1,2], and fertigation is regarded as an effective solution [2]. According to Fan et al [3], fertigation can keep the output unchanged, while saving 30-50% fertilizers and 50% water.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The high price of fertilizer will reduce income due to the high use of fertilizers [16]. The farmers who follow the guidelines in the use of fertilizers will get higher crop yields and incomes will increase [17]. Therefore the combination of chemical and organic fertilizers is suggested and highly practiced by the farmers [18].…”
Section: Resultsmentioning
confidence: 99%